DIPLOMASI BUDAYA PEMERINTAH PROVINSI KALIMANTAN SELATAN DALAM FESTIVAL BANJAR 2018-2019 - Salsabila Andi Akil; Indra Kusumawardhana (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
Indonesia conduct cultural diplomacy activities not only by central government but also regional government, including Provincial Government of South Kalimantan. The purpose of this research is to understand how Provincial Government of South Kalimantan conducted cultural diplomacy in Festival Banjar 2018-2019. The concepts used in this research are Cultural Diplomacy by Gienow-Hecht and Donfried and Paradiplomacy by Duchacek. This research uses constructivist paradigm and qualitative research method with qualitative data analysis techniques by Miles, Huberman and Saldana. The results of this research reveal that Festival Banjar 2018-2019 is a form of cultural diplomacy carried out by sub-national actor, in this case Provincial Government of South Kalimantan. Festival Banjar 2018-2019 is a cultural diplomacy agent practice belongs to mixed model; agenda to promote South Kalimantan culture and tourism; vehicle through South Kalimantan art and floating market simulation; target audience are the diplomatic corps and foreign societies. Provincial Government of South Kalimantan as a sub-national actor also related to paradiplomacy where the implementation involves two main types of paradiplomatic activities, such as lobbying through interactive talk shows with the target audiences; and media exposure during the event.